Social Responsibility Satoe Indonesia in Order to Improve the Quality of Education in Papakmanggu Village - Luthfi, Muhammad; Rudito, Bambang (Journal of Business and Management, 2014)
Researchers do an analysis of the ability of a child who has graduated from PAUD Program Ã‚Â at Rumah Pintar Papakmanggu, in Kampung Papakmanggu, Desa Cibodas, Kecamatan Pasirjambu, Kabupaten Bandung to get picture in detail how conditions PAUD graduate who has entered the primary school level. Researchers will conduct interviews to teachers SDN Papakmanggu, where all the PAUD graduates school there. The result from this study is, PAUD in Rumah Pintar Papakmanggu. Research that has been carried out, explaining that PAUD programs have provided positive for a change to the children who attend PAUD programs for free, this is evidenced by the results of research conducted on teacher elementary in Papakmanggu on the ability of children who attend PAUD states that children who attend PAUD has advantages in terms of cognitive aspects such as having the ability to read, write, and count is not owned by a child who does not follow the PAUD.Keyword: PAUD, Social Responsibilty, Rumah Pintar, Satoe Indonesia, and Early Childhood